ANALISIS FRAUD RESPONSE DAN FRAUD RECOVERY SYSTEM PADA LEMBAGA KEUANGAN MIKRO: PENDEKATAN STUDI KASUS - Nurani, Bulan Karima; Jayanti, Fitri Dwi; Tantra, Arda Raditya (Faculty of Economic and Business Universitas STIKUBANK, 2024)
This study aims to determine the considerations used by management in fraud response to cases that have harmed cooperatives and customers, and to determine the loss recovery system taken by management. The subjects and organizations studied are the management of a microfinance institution (ABC Cooperative) in Central Java. The objectives of this study will be achieved by using a qualitative research design, with a case study approach. Case studies are chosen because the unit of analysis is one organization. Analytical research is used to explore how and why a phenomenon occurs. The results of this study explain that the response taken by the cooperative to cases of fraud committed by its employees is termination of employment with several agreements, without involving the legal process. This step is taken to maintain the good name of the Cooperative in the eyes of the public and minimize the expenditure of larger funds. In practice, this study proves and strengthens the theory that most fraud committed by employees is undetected and is often resolved secretly to protect the victim's good name, this estimate is likely to underestimate the actual losses to business and society. This study can also provide practical implications for other cooperative institutions as a reference in making decisions related to similar cases.